Single Subcutaneous Injection of Lysophosphatidyl-Choline Evokes ASIC3-Dependent Increases of Spinal Dorsal Horn Neuron Activity - Pidoux, Ludivine; Delanoe, Kevin; Barbier, Julie; Marchand, Fabien; Lingueglia, Eric; Deval, Emmanuel (Frontiers in Molecular Neuroscience, 2022)
Lysophosphatidyl-choline (LPC), a member of the phospholipid family, is an emerging player in pain. It is known to modulate different pain-related ion channels, including Acid-Sensing Ion Channel 3 (ASIC3), a cationic channel mainly expressed in peripheral sensory neurons. LPC potentiates ASIC3 current evoked by mild acidifications, but can also activate the channel at physiological pH. Very recently, LPC has been associated to chronic pain in patients suffering from fibromyalgia or osteoarthritis. Accordingly, repetitive injections of LPC within mouse muscle or joint generate both persistent pain-like and anxiety-like behaviors in an ASIC3-dependent manner. LPC has also been reported to generate acute pain behaviors when injected intraplantarly in rodents. Here, we explore the mechanism of action of a single cutaneous injection of LPC by studying its effects on spinal dorsal horn neurons. We combine pharmacological, molecular and functional approaches including in vitro patch clamp recordings and in vivo recordings of spinal neuronal activity. We show that a single cutaneous injection of LPC exclusively affects the nociceptive pathway, inducing an ASIC3-dependent sensitization of nociceptive fibers that leads to hyperexcitabilities of both high threshold (HT) and wide dynamic range (WDR) spinal neurons. ASIC3 is involved in LPC-induced increase of WDR neuron’s windup as well as in WDR and HT neuron’s mechanical hypersensitivity, and it participates, together with TRPV1, to HT neuron’s thermal hypersensitivity. The nociceptive input induced by a single LPC cutaneous rather induces short-term sensitization, contrary to previously described injections in muscle and joint. If the effects of peripheral LPC on nociceptive pathways appear to mainly depend on peripheral ASIC3 channels, their consequences on pain may also depend on the tissue injected. Our findings contribute to a better understanding of the nociceptive signaling pathway activated by peripheral LPC via ASIC3 channels, which is an important step regarding the ASIC3-dependent roles of this phospholipid in acute and chronic pain conditions.